Cleavage of Unstrained C−C Bonds in Acenes by Boron and Light: Transformation of Naphthalene into Benzoborepin. Issue 4 (20th December 2017) - Wang, Suning; Yuan, Kang; Hu, Ming‐Feng; Wang, Xiang; Peng, Tai; Wang, Nan; Li, Quan‐Song
Abstract: Naphthalene and acenaphthene with peri 2‐py and BMes2 (py=pyridyl, Mes=mesityl) substituents have been found to undergo facile phototransformation, cleavage of a C−C bond of naphthalene, and formation of 2‐py‐bound benzoborepins as the major products. Mechanistic pathways of this photoreaction have been established by examination of both excited and ground states by using CASSCF and CASPT2 methods in DFT and time‐dependent DFT calculations. The mesityl to py‐naphthyl charge‐transfer transition and the mesityl migration from the boron atom to the naphthyl moiety drive this unprecedented C−C bond cleavage and boron‐insertion reaction. Abstract : Cleavage of unstrained arene C−C bonds has been established in boron‐functionalized naphthalene and its derivatives. The method provides a new and convenient approach for the synthesis of borepin molecules. Mes=Mesityl.